Internet service providers' liability on defamation / Siti Aisyah Ahmad, Nurul Diyana Hijazi Abidin Jali Hijazi and Wan Farrah Farriza Wan Ghazali. - Ahmad, Siti Aisyah; Abidin Jali Hijazi, Nurul Diyana Hijazi; Wan Ghazali, Wan Farrah Farriza (Faculty of Law, 2007)
This paper presents a study on the Internet Service Providers (ISPs) liability on defamation. The aim of the paper is to analyse the liability of the Internet Service Providers (ISPs) for online defamation, where the defamatory statement are being disseminated through the Internet Service Providers (ISPs) services. As Internet becomes more popular each day and the users of the Internet increase day by day, we are threatened with online crimes especially on defamatory statements as it can be easily publish worldwide with just one 'click'. Whether the Internet Service Providers (ISPs) can be held liable for online defamation through their services is the issue that arises regarding this matter. To say that the ISPs are wholly liable is unjust as it is impractical to expect an Internet Service Providers to monitor all the services that they are providing. Thus, this study recommend new provisions that can be included in the existing law of this country, such as Penal Code, Defamation Act 1996, Communication and Multimedia Act 1998 that can be considered in order to clarify whether ISPs can be liable or not be liable on defamation with the hope to control. Insya- Allah.